The validity and reliability of the jump power app for measuring vertical jump actions in professional soccer players - Onat Çetin; Selman Kaya; Gökhan Atasever; Zeki Akyildiz (Scientific Reports)
Abstract This research examines the reliability, validity, and usefulness of the Jump Power application by comparing it with the reliable and validated Optojump photoelectric cell system in measuring squat jump (SJ) and countermovement jump (CMJ) in professional athletes. Twenty-two soccer players volunteered to participate in the research. The participants were the players of the U21 team in the 1st League. All athletes were subjected to SJ and CMJ tests. Jump Power app and Optojump data were acquired simultaneously during SJ and CMJ. Trial procedure was performed on three separate occasions (Session 1, Session 2, and Session 3), with 48 h intervals to examine the reliability of the data from session to session. For reliability analysis, coefficients of variation percent (%CV). Jump power app reliability values CV% is below 5%. In the validity analysis, significant differences were observed between the Optojump photoelectric cell system and the Jump Power App for SJ and CMJ. In conclusion, this study revealed that the Jump Power app is a reliable but not valid tool to measure vertical jumps in soccer players.